2011
DOI: 10.1002/art.30201
|View full text |Cite
|
Sign up to set email alerts
|

TSG‐6 inhibits osteoclast activity via an autocrine mechanism and is functionally synergistic with osteoprotegerin

Abstract: Objective. TSG-6 (the product of tumor necrosis factor [TNF]-stimulated gene 6) has a potent inhibitory effect on RANKL-mediated bone erosion. The aim of this study was to compare the activity of TSG-6 with that of osteoprotegerin (OPG) and to investigate its role as an autocrine modulator of cytokine-mediated osteoclast formation/activation. We also determined TSG-6 expression in inflammatory joint disease.Methods. The effects of TSG-6, OPG, and the inflammation mediators TNF␣, interleukin-1 (IL-1), and IL-6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 97 publications
(76 reference statements)
7
36
0
Order By: Relevance
“…In addition the following upregulated genes may support bone growth by interfering with osteoclast activity: tumor necrosis factor, alpha-induced protein 6, TNFAIP6/TSG6 (FC 4.84) [89], and serpin peptidase inhibitor, clade F member 1, SERPINF1/PEDF (FC 4.77).…”
Section: Resultsmentioning
confidence: 99%
“…In addition the following upregulated genes may support bone growth by interfering with osteoclast activity: tumor necrosis factor, alpha-induced protein 6, TNFAIP6/TSG6 (FC 4.84) [89], and serpin peptidase inhibitor, clade F member 1, SERPINF1/PEDF (FC 4.77).…”
Section: Resultsmentioning
confidence: 99%
“…7) also showed anti-bone resorption of TSG-6-modified iPS-MSCs by suppressing osteoclast formation and inhibiting alveolar bone resorption in this investigation. Previous study has shown that TSG-6 could regulate bone remodeling though the inhibition of osteoclast activity and the synergistic formation with osteoprotegerin [18], [19]. They indicated an autocrine mechanism of TSG-6 inhibiting osteoclasts activation; that is, osteoclast precursors and mature osteoclasts produced TSG-6 in response to pro-inflammatory cytokines (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Among these factors, the most interesting was tumor necrosis factor alpha-stimulated gene-6 (TSG-6) [12], which has been extensively studied in articular joint diseases [13][15]. The anti-inflammatory and chondroprotective effects of TSG-6 have been reported in numerous animal models [16][19]. However, the combined effect of MSCs and TSG-6 has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…TSG-6 is composed of two domains: the Link module with its HA-binding domain (3134) and the CUB module (Protein Data Bank entry 2WNO) (35). In some cases, the Link module has been found to elicit biological responses similar to full-length TSG-6 (3639). However, this is not the case for the interaction with HA; the Link module alone binds to HA in a simple manner, whereas the full-length protein binds to HA cooperatively, due to HA-induced TSG-6 oligomerization, a process that leads to cross-linking of HA (40).…”
Section: Introductionmentioning
confidence: 99%